2011
DOI: 10.1007/s12020-011-9454-5
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter syndrome and short stature: an unusual combination

Abstract: Klinefelter syndrome is not easy to diagnose in childhood because of the absence of significant manifestations before puberty. Three main clinical signs should suggest the diagnosis in a child: small testes, tall stature, and mental retardation or learning problems. We present a patient with Klinefelter syndrome and short stature due to growth hormone deficiency. His height was below the third percentile for age and his bone age delayed. Maximal serum GH levels after insulin-induced hypoglycemia and clonidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Rossodivita et al ( 6 ) reported an 8-year-old boy with short stature and cryptorchidism who was later diagnosed to have KS and GH deficiency. Bahillo Curieses et al ( 7 ) reported a similar combination in a child receiving GH therapy when evaluated for delayed puberty, but the brain MRI was reported as normal in this patient. Ben-Skowronek et al ( 8 ) and Tori et al ( 9 ) also reported similar combination of KS and GH deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Rossodivita et al ( 6 ) reported an 8-year-old boy with short stature and cryptorchidism who was later diagnosed to have KS and GH deficiency. Bahillo Curieses et al ( 7 ) reported a similar combination in a child receiving GH therapy when evaluated for delayed puberty, but the brain MRI was reported as normal in this patient. Ben-Skowronek et al ( 8 ) and Tori et al ( 9 ) also reported similar combination of KS and GH deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…In our cohort, only one case, who had also a prenatal diagnosis, presented with short stature when he was aged three years. There are a few reported cases of KS with short stature, secondary to growth hormone deficiency ( 14 , 15 ). However, we did not detect growth hormone deficiency in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…In children, work up is usually done in patients with tall stature and gynecomastia in combination with a learning disability. Although tall stature, with slender body habitus is one of the most common clinical finding of patients with KS, some uncommon variants are associated with short stature (49 XXXXXY, isochrome Xq) [1]. Few reported cases of KS has been reported in patients with short stature due to growth hormone deficiency [1,2].…”
Section: Discussionmentioning
confidence: 99%